Selayang Kritik atas Keberadaan Staff Khusus Milenial Presiden Jokowi - Sayyidatiihayaa Raseukiy (Padjadjaran Law Review, 2022)
The existence of the Special Staff of President Joko "Jokowi" Widodo in the second cabinet created controversy. One of the biggest sounds is the assumption that the President's Millennial Special Staff was created without a clear authority and functions, which escalated to the overlap of sectoral authority between government agencies. In addition, many parties considered that instead of performing well, the President's Millennial Special Staff actually took many counterproductive actions to disrupt the bureaucratic flow of the executive branch. This article will try to find a rational reason why even though the existence of the Millennial Staff has brought a lot of criticism, Joko Widodo still employs them. I will try to be traced by opening a bridge between Joko Widodo's policy preferences and the formation of Millennial Staff. So that there is a scientific assessment of the needs of the Presidential Special Staff in the presidential system— which mandates a large “burden” on the shoulders of the President as Head of Government and Head of State.